Identification of rsbA Gene in Proteus Mirabilis Isolated from Patients with Respiratory Tract Infections and Determining their Antibiotic Resistance - Shanay A. Mohammed; Yokcil I. Sowaid; Goljameen Midhat Abdulla (American Journal of Biology and Natural Sciences, 2025)
Background & aim: P. mirabilis rarely causes lung infections or pneumonia, and it usually affects people who have chronic lung illness or chronic debilitation. The current study was conducted to determine the antibiotic resistance of P. mirabilis isolated from individuals with respiratory tract infections by identifying the rsbA gene. Materials & methods: From January to July 2025, 270 specimens were taken from outpatients with respiratory tract infections who were exhibiting symptoms and visiting hospitals and private clinics in Kirkuk City. PCR was utilized to diagnose the rsbA gene, and each specimen was identified by phenotypic traits after being cultivated on various labeled culture media. Results: The results indicated that when P. mirabilis was grown on MacConkey agar, 28 (10.4%) of the total specimens had positive growth results. On the other hand, the results showed that 243 (89.3%) of sputum samples were negative for bacterial growth of P. mirabilis out of a total of 270 samples. Biochemical tests for P. mirabilis bacteria appear to be negative for Indole, oxidase, while, P. mirabilis were positive for urease, citrate, motility, catalase and Kligler iron k/A H2S. P. mirabilis showed a high resistance toward 78.6% Ceftriaxone, 85.7% Cefepime and 96.4% Ampicillin. Otherwise, P. mirabilis showed high sensitive toward 71.4% Gentamicin, 78.6% Imipenem, and 78.6% Amikacin respectively. After isolating DNA from P. mirabilis using an extraction and electrophoresis kit, it was found that 100% of P. mirabilis isolates contained the rsbA gene. Conclusions: It is concluded from the results of the current work that Proteus mirabilis is one of the causes of respiratory tract infections and has shown high resistance to antibiotics. One of the most important reasons for its virulence is that it possesses virulence genes in high proportions. The study also showed that the bacteria possessed 100% of the rsbA gene, which is responsible for regulating swarming motility.